(Un)equal Educational Opportunities and the Labor Market: A Theoretical Analysis. (19th May 2017) - Benegas, Maurício; Corrêa, Márcio Veras
Abstract: This paper intends to study the effects of public school quality offer on the labor market performance. With this objective in mind, we build a matching model for the labor market in two sectors: schooled and non‐schooled. The skilled segment of the economy is endogenous and composed of a continuum of workers who differ in the quality of the school attended. We show that there is a trade‐off between the quantity and the quality of education and that a reduction in schooling costs increases school enrollment rates. However, it adversely reduces the job creation dynamics in the skilled sector, due to the Composition Effect . We also verify that a first order improvement in school quality distribution may generate an increase in the schooling rate and a greater job vacancy creation in the skilled sector with no negative effects on the unskilled sector.